(untitled) (Alternautas, 2022)
The 2017 Atlantic Hurricane Season brought forth multiple storms that not only stripped trees bare and dismounted roofs, but it also caught the Caribbean and Gulf Coast unprepared for the magnitude of destruction that such storms could bring, despite the best efforts of the messengers. Nearly half a year after the last hurricane season and half a year away from the onset of the next one, stories about the damage that Hurricane Irma and Maria caused have become hauntingly familiar. The stories less often told, though, are those about the long-term recovery efforts that have inevitably followed since the seas have calmed and the winds have died down.